Preparation of State Standards of Azerbaijan National Musical Instruments - Lale Hüseynova; Mammadali Mammadov (Art Time)
The musical instruments used in Azerbaijani national music have been passed down from generation to generation for centuries and have survived to the present day. Since ancient times, the people of Azerbaijan have kept the saz musical instrument alive. Our tar, kemenche, saz and other musical instruments are in need of development and revival today. The main purpose of the scientific article titled "Preparation of the State Standard of Azerbaijani National Musical Instruments (Tar, Saz)" that we present is aimed at solving this problem. This article includes the classification of Azerbaijani folk music instruments, their proportional calculations, problems and their elimination, which we have been researching for years. In the article, the replacement and development of tar and saz national musical instruments in new formats and new proportions are mentioned. Here, both musical instruments are classified on the basis of tables and diagrams.As we noted in the article, efforts to constantly adopt some of our national musical instruments (balaban, qanun) by others and to present these instruments as their own on a world scale continue today. Our main goal is to preserve our national musical instruments, to revive and develop these instruments and to exhibit their characteristics, and to determine their place and importance in the development of our national musical culture. In our presented scientific article, we are trying to achieve our goal based on important analysis and evidence.